Fashion Giants Looking Good, Doing Good? Corporate Social Responsibility of Leading Fashion Companies - Wand, Susanne Elisabeth (2015)
The purpose of this dissertation is to explore the relationship between leading fashion companies and their communicating initiatives with respect to any efforts in corporate social responsibility. For this reason the following objectives were proposed: To identify the corporate social responsibility segments where fashion firms recognise strengths and opportunities. To profile these depending on performance, geographical disparities, year of foundation and communication channels. And to evaluate whether communication initiatives by leading fashion companies are mature enough to become predominant standards among the industry. The study conducted a content analysis on publicly available information by leading fashion companies. This was guided by a self-developed score sheet compiled from 151 assessment criteria, which were evaluated utilising an ordinal scale from 1 through 5. Post-data collection was followed by the analysis using the Kolmogorov-Smirnov test to check for normal Gaussian distribution, the Mann-Whitney tests to detect differences between two independent conditions, the Wilcoxon signed-rank test to investigate two related conditions and, finally the Kruskal-Wallis test in to check for differences between independent groups. The analysis identified two independent variables that significantly impact communication initiatives by leading fashion companies. Furthermore, implications of strengths and weaknesses are provided along with valuable recommendations for organisations within the fashion industry and beyond. Few studies have examined corporate social responsibility communication initiatives by fashion companies. Studies without the industry focus have not harnessed evaluation score sheets in a comparative content analysis. With the increasing prominence of labour issues and resource scarcity,this paper is important to academic researchers, fashion companies and parties involved in the upstream and downstream value chains.